2018
DOI: 10.4314/mmj.v30i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric nephrectomy: Patterns, indications and outcome in a developing country

Abstract: BackgroundPatterns of and indications for nephrectomy vary in different age groups, geographical locations and time periods. In some series nephrectomies were mainly for malignant conditions while in others they were predominantly for non-malignant conditions. Such data on patterns, indications, and outcomes of nephrectomy in children is limited in our environment.ObjectivesTo evaluate nephrectomy in childhood at the Sub-Department of Pediatric Surgery University of Nigeria Teaching Hospital, Ituku/Ozalla Enug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…One study from Enugu, Nigeria reported that nonmalignant indications for nephrectomy were more in females [2]. Our patients' mean age of 6 years is consistent with the report of Bouhafs et al but at variance with the report of Sammond et al [13,14].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One study from Enugu, Nigeria reported that nonmalignant indications for nephrectomy were more in females [2]. Our patients' mean age of 6 years is consistent with the report of Bouhafs et al but at variance with the report of Sammond et al [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, there were more nephrectomies in males than in females. Other series on pediatric nephrectomy also reported this male predominance [2,11]. However, other studies documented more nephrectomies in females [7,12].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The observed obstruction in this patient must have been of long standing, considering the extent of destruction of the parenchyma of the corresponding renal moiety. Such late presentation with non-functioning corresponding renal moiety necessitating heminephrectomy has been reported in our environment, but mostly in children (10). In the absence of any significant renal tissue in the grossly hydronephrotic upper renal moiety, excision of the redundant hydronephrotic sac with the dilated ureter poses no major challenge.…”
Section: Discussionmentioning
confidence: 86%
“…La cirugía es el tratamiento de elección. Está contraindicada cuando el tumor infiltra la vena Cava, o cuando sobrepasa la línea media del abdomen (por el riesgo de que se rompa y contamine la cavidad abdominal) (Ezomike et al, 2018). A 21 pacientes (58,3 %) se les realizó CI, y cuando se sumaron los pacientes con QTNA fueron intervenidos 33 pacientes (91,67 %).…”
Section: Discussionunclassified